The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1093/protein/gzh043
|View full text |Cite
|
Sign up to set email alerts
|

Finding a new vaccine in the ricin protein fold

Abstract: Previous attempts to produce a vaccine for ricin toxin have been hampered by safety concerns arising from residual toxicity and the undesirable aggregation or precipitation caused by exposure of hydrophobic surfaces on the ricin A-chain (RTA) in the absence of its natural B-chain partner. We undertook a structure-based solution to this problem by reversing evolutionary selection on the 'ribosome inactivat-ing protein' fold of RTA to arrive at a non-functional, compacted single-domain scaffold (sequence RTA1-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 5 publications
3
61
0
2
Order By: Relevance
“…The authors reported no signs of ricin intoxication though they did not present any data concerning lung function or tissue damage. The other recombinant RTA vaccine contains two large deletions, to eliminate the enzymatic activity as well as to remove a hydrophobic region (normally associated with RTB in the holotoxin) to make the vaccine more stable and soluble [ 32 ]. This vaccine administered i.m., with or without adjuvant, protected mice against lethal ricin challenges given either i.p.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported no signs of ricin intoxication though they did not present any data concerning lung function or tissue damage. The other recombinant RTA vaccine contains two large deletions, to eliminate the enzymatic activity as well as to remove a hydrophobic region (normally associated with RTB in the holotoxin) to make the vaccine more stable and soluble [ 32 ]. This vaccine administered i.m., with or without adjuvant, protected mice against lethal ricin challenges given either i.p.…”
Section: Discussionmentioning
confidence: 99%
“…As described further below, the broad nature of C v over the wide range of temperatures indicates that the model for unfolding-folding is nearly continuous and lacks significant cooperativity, leading to what can best be described as a polyamorphic transition between a highly-frustrated ''glassy'' state and a configurationally labile protein. 27,28 While the SICHO model may not have realistically reproduced the high-resolution calorimetric features of the RTA molecules, the difference given by DT f between the two structures is approximately 8 K and is in remarkable concurrence with the experimental determination of roughly 7 K. 16,17 This correct prediction of a small change in protein stability needs, however, to be cautiously weighted by the ambiguity in determining T f from a broad C v function. Although each heat capacity has converged from Monte Carlo sampling over 5 3 10 10 lattice configurations and the error in the WHAM numerical 16 The bumps in the all-atom C v are an artifact of the high T conversion.…”
Section: Methodsmentioning
confidence: 99%
“…We designate this modeled structure as RTA1-33/44-198. 16 The remaining two modeled structures are RTA with residues located in the C-terminal region 199-267 replaced with the hydrophobic residue Ile (the protein chain is denoted as RTA-Ile), and the second are the same residues replaced with the sequence corresponding to pokeweed antivirus protein (PAP), using a structure-structure alignment with the PDB structure 1pag. We denote our hybrid as RTA/PAP.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations